PEMANFAATAN TAMAN HUTAN KOTA BNI BANDA ACEH SEBAGAI MEDIA PEMBELAJARAN KONSEP DUNIA TUMBUHAN (KINGDOM PLANTAE) PADA SISWA SMA - Hasanuddin; Misnilianda; Wendi Septian (Biotik, 2015)
This study aims to find out the effect of Utilizing BNI Forest City Parkof Banda Aceh as Learning Media in the Concept of World Plants (Kingdom Plantae) to the learning outcome of high school students of Class X-IA. The sample of this research was students class X-IA1 as the experimental class and students class X-IA2 as the control class. The data obtained by giving the test to the students by using experimental research methods. The data were analyzed by using t-test formula. The results showed that the value oft =4.12>table =2.03, sothe hypothesis which was stated that â€œthere was influence of the use of BNI Forest city park of Banda Aceh as learning media to ward the learning out comes of students classX-IA of SMAN 5 Banda Aceh in learning the concept of the plant world (Kingdom Plantae)â€ is accepted. It can be concluded that theuse of BNI Forest city Park Banda Aceh as learning mediain fluences the studentsâ€™ learning outcomes in learning the concept ofthe plant world (Kingdom Plantae) in classX-IA of High School.